3D extruded composite thermoelectric threads for flexible energy harvesting - J. Peng (Nature Portfolio, 2019)
Flexible thermoelectric composite threads are reported for wearable thermal energy harvesting platforms where rigid materials lack compatibility. Thermoelectric thread modules are demonstrated, and pressure-dependence shows thread compression to be essential for improving electrical conductivity.